Objective first. Teacher's book - Capel, Annette (Cambridge : Cambridge University Press, 2012)
Third edition of the best-selling Cambridge English: First (FCE) course.
Keywords: English language -- Textbooks for foreign speakers; English language -- Examinations -- Study guides. -- Study guides; English language -- Problems, exercises, etc